Coronary Artery Disease in Patients with Chronic Kidney Disease - A Review - Faruque, M; Islam, AEM M; Rashid, MA; Haque, MS; Rahman, F; Kibria, MG; Khan, HILR (Cardiovascular Journal, 2011)
DOI: http://dx.doi.org/10.3329/cardio.v1i1.8212 Cardiovasc. j. 2008; 1(1) : 97-104